Electrophysiological Changes in Leprous Patiants - Akyatan, Nevzat; Harmanyeri, Yavuz; Gürtekin, Yaşar; Doğruöz, Keramettin; Yardım, Muzaffer (European Journal of Therapeutics, 1990)
Conduction velocities of 15 ulnar, 4 peroneal, 3 median and 1 sural nerve were investigated and needle EMG were performed in related muscles in 14 leprous patients. Seven of them were in lepromatous, 3 of them were borderline and 4 of them were in tuberculoid leprous group. Axonal değeneration findings were found in the nerves especially in Tuberculoid leprous group with demiyelinization findings. Ulnar nerve conductior. velocity impairment was found tletween the wrist and 5 th digit as frequently as in the elbow segment.